Changes for Felicity : a winter story - Tripp, Valerie, 1951- (American girls collection., 1992)
The outbreak of the Revolutionary War in 1775 brings drastic changes to Felicity's life in Williamsburg, affecting both her family and her friendship with Elizabeth.